Introduction to IPv6: The need and the advantages of IPv6 - Shibghatullah, Abdul Samad; Hamid , Erman; Bahaman, Nazrulazhar; Mas'ud, Mohd Zaki (2008)
The IP (Internet Protocol) currently used in networks and the Internet is IP version 4 (IPv4). In the last ten years, the Internet has transformed the way people live. The Internet’s tremendous growth rate greatly exceeded any futurist's predictions. Therefore, the new version, called IP version 6 (IPv6), resolves unanticipated IPv4 design issues and takes the Internet into the 2Ist Century. This paper describes the introduction, history and the advantages of IPv6. Some of the advantages are IPv6 offers numerous advantages over IPv4. In this section we will discuss the most prominent ones that are larger address space, faster routing, mobility, quality of service, security, and auto conﬁguration of hosts.